The CSR Strategy of The Body Shop before and after Acquisition--A case study analysis - Liu, Boni (2008)
The Body Shop is one of the leading companies which related its business value with the environment concerned. Furthermore, it influences other companies, which are not only in the cosmetic industry, but also in industries as retail industry, transportation industry and so on. However, most of the articles and journals only consider The Body Shop as an example of ethical business model but lack of in-depth analysis of the motivation behind its CSR strategies. In addition, there are few in-depth research papers to analyse The Body Shop performance after it was acquired by LÃÂÃÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂOreal. Therefore, I will apply strategic models to evaluate the motivation of The Body Shop to carry out its CSR strategy based on its market and non-market environment. Then, I will also try to evaluate the performance changes after the acquisition with LÃÂÃÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂOreal. Finally, I will provide some insights that arise from this case to help other companies, which are in the similar situation as The Body Shop.